2014
DOI: 10.1080/0144235x.2014.974355
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and cytotoxic effects ofArtemisia herba-albaon mammalian cells

Abstract: Artemisia herba-alba is a medicinal plant that is commonly used in folk remedies in the Middle East. Despite its wide use, little is known about whether or not it is genotoxic and/or cytotoxic to mammalian cells. Here we investigated the genotoxic and cytotoxic effects of the ethanolic plant extract on mice cells at different dose concentrations (125, 250, 375, and 500 μg ml ) and for different exposure times (12, 24, 48, and 72 h). We found that at all exposure times, treatment with high dose concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Our results showed that 5 out of 21 plants used by the Moroccan population for treating or preventing COVID-19 were listed to be toxic (Table 5). Concerning the toxicity of Artemisia herba-alba, a study by Abderrahman and Shbailat showed harmful effects on the division of bone marrow cells and the induction of chromatid exchanges at doses of 375 and 500 μg ml − 1 [30], while another study mentioned the potential renal toxicity of this plant [31]. N. oleander is known for its toxicity due to the presence of cardiac glycosides in all plant parts.…”
Section: Toxic Plantsmentioning
confidence: 99%
“…Our results showed that 5 out of 21 plants used by the Moroccan population for treating or preventing COVID-19 were listed to be toxic (Table 5). Concerning the toxicity of Artemisia herba-alba, a study by Abderrahman and Shbailat showed harmful effects on the division of bone marrow cells and the induction of chromatid exchanges at doses of 375 and 500 μg ml − 1 [30], while another study mentioned the potential renal toxicity of this plant [31]. N. oleander is known for its toxicity due to the presence of cardiac glycosides in all plant parts.…”
Section: Toxic Plantsmentioning
confidence: 99%
“…Despite the promising therapeutic potential of the cited species, informants were fully aware of the possible consequences of overuse and drug interactions, particularly in the case P. harmala and A. herba alba . This belief is supported by convincing arguments regarding the safety of both species as they have been reported to cause side effects in animal and human case reports [70,71,72]. Importantly, some of the side effects may also be due to herb–drug interactions, especially, that the concurrent use of both traditional and pharmaceutical medications for treating hypertension or other chronic diseases is a worldwide tendency [73].…”
Section: Discussionmentioning
confidence: 99%
“…BrdU tablets were compressed using pellet press (Parr Instrument Company, Moline, ILLinois, USA) equipped with punch of 0.178” diameter as described by Allen et al[ 17 18 ] Portions of 200 mg mounting powder were mixed with the BrdU dye, and firmly pressed to maintain consistent compaction, hence dissolution rate among tablets. Tablets were kept in a freezer until used.…”
Section: Methodsmentioning
confidence: 99%